Actigraphy Measured Sleep Indices and Adiposity: The Multi-Ethnic Study of Atherosclerosis (MESA) - Ogilvie, Rachel P. (Sleep, 2016)
STUDY OBJECTIVES: To investigate the cross-sectional relationship between objectively measured sleep characteristics and multiple indices of adiposity in racially/ethnically diverse older adults within the MESA Sleep study (n = 2,146). METHODS: 7-day actigraphy was used to assess sleep duration, sleep efficiency, and night-to-night variability. Body mass index (BMI), waist circumference, and total body fat were modeled continuously and according to obesity cut-points. Models were adjusted for demographic, socioeconomic, and behavioral variables. RESULTS: Participants who slept less than 6 hours a night had significantly higher BMI, waist circumference, and body fat relative to those who slept 7–8 hours. Those who slept less than 5 hours had a 16% higher prevalence of general obesity (BMI ≥ 30 vs. < 25 kg/m(2)) (95% [CI]: 0.08–0.24) and a 9% higher prevalence of abdominal obesity (waist circumference: women ≥ 88 centimeters, men ≥ 102 centimeters; 95% CI: 0.03–0.16) compared to those who slept 7–8 hours. Results were similar for sleep efficiency and night-to-night sleep variability. CONCLUSIONS: Among an older multi-ethnic cohort, we found robust associations across multiple indices of sleep and adiposity. Targeting sleep characteristics may be of benefit in obesity interventions, but more research is needed to rule out reverse causality. CITATION: Ogilvie RP, Redline S, Bertoni AG, Chen X, Ouyang P, Szklo M, Lutsey PL. Actigraphy measured sleep indices and adiposity: the Multi-Ethnic Study of Atherosclerosis (MESA). SLEEP 2016;39(9):1701–1708.